TEMPORAL VARIATIONS IN BOVINE FEEDING: INSIGHTS FROM COWS AND CALVES AT NEUDAMM FARM, NAMIBIA - Petrus , Tuwilika Amadhila (Ayden Journal of Agriculture and Allied Studies, 2025)
Agriculture in Namibia faces significant challenges, including a shortage of moisture, erratic rainfall patterns, frequent droughts, and low literacy levels among farmers, compounded by inadequate management skills. Despite contributing a modest portion (just over 4%) to Namibia's Gross Domestic Product (GDP) in recent years, agriculture remains a cornerstone of the nation's economy due to its vital role in providing livelihoods for the predominantly rural population and generating foreign exchange. The agricultural sector is predominantly reliant on extensive livestock ranching, particularly cattle, goats, and sheep. Cattle farming, in particular, is managed with minimal external inputs, relying mainly on natural vegetation, and supplementation is only provided to address nutritional deficiencies in the forage. This system of livestock ranching is at risk due to the variable environmental conditions and the challenges faced in managing limited resources effectively. This paper explores the constraints on agricultural productivity in Namibia, with an emphasis on livestock farming, and highlights the need for improved agricultural management practices and adaptation strategies to mitigate the effects of environmental challenges and ensure sustainability